Study Habits of Undergraduate Medical Students in Bangladesh (Bangladesh Journal of Medical Education, 2023)
The study habits of students are the most important factors that influence the performance of students. Poor study habits are considered one of the main causes of students’ academic failure and can have an important impact on their education and their occupational prospect. Currently, no time bound and elaborative research is found to identify the study habits of undergraduate medical students in Bangladesh. This descriptive-type of cross-sectional study was conducted in different medical colleges with the objective to find out the study habits of undergraduate medical students of Bangladesh. It also aimed to find out if there is any difference in study habits between the students with high, average and below-average grade achievers in professional examinations. Data were collected from 586 conveniently selected students from 10 government and 9 private medical colleges of Bangladesh within the period of one year. A pretested semi-structured, self-administered questionnaire was used for data collection. Study habits were assessed in seven domains namely textbook reading, note-taking, memorizing lessons, paying concentration, exam /test preparation, time management, and classroom-related activities. With regards to study habits, it was revealed that undergraduate medical students have an average study habit score in textbook reading (3.54±1.14), note taking (3.33±1.17), memorizing lessons (3.35±1.17), preparation for the test (3.53±1.18), time management (3.40±1.18) and classroom related activities (3.22±1.2) domains. There is a significant difference in study habit score of high grades and below-average grade achievers in professional examinations. This average score of study habits was below our expectations. This study recommended that teachers should make an effort to develop or improve the study habits of medical students by acquainting them with good and poor/ bad study habits. So that students can identify their poor study habits and can take the appropriate remedial measure. Teachers can guide weak students to develop effective study habits so that students’ learning can be enhanced.Bangladesh Journal of Medical Education Vol.14(2) July 2023: 45-55